2016
DOI: 10.1097/md.0000000000004328
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of growth-regulated oncogene-alpha in tumor and stromal cells predicts unfavorable prognosis in pancreatic cancer

Abstract: Growth-regulated oncogene-alpha (GRO-α) has been reported to be over-expressed in a series of human cancers including colorectal cancer, melanoma, gastric cancer, hepatocellular carcinoma, and ovarian cancer and was known to regulate multiple biologic activities associated with tumor progression. But the role in human pancreatic cancer remains unclear. To examine the expression of GRO-α and its clinical significance in pancreatic cancer (PC), a total of 12 fresh PC specimens and 12 surrounding normal tissues t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Certain studies have suggested that patients with pancreatic, gastric or hepatocellular cancer exhibit increased levels of CXCL1 in cancer tissues (38-40). By contrast, other studies have demonstrated that CXCL1 mRNA expression levels in hepatic tumors were similar between cancerous and non-cancerous tissues (41).…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have suggested that patients with pancreatic, gastric or hepatocellular cancer exhibit increased levels of CXCL1 in cancer tissues (38-40). By contrast, other studies have demonstrated that CXCL1 mRNA expression levels in hepatic tumors were similar between cancerous and non-cancerous tissues (41).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical significance to growth-regulated oncogene- α has been assigned by Lian and collaborators. In a recent study, they observed higher level of this chemokine in pancreatic cancer tissues as compared to normal ones, and the expression was correlated with TNM stage and metastases localization, thus leading to significant poor survival of patients [105].…”
Section: The Role Of Cytokines In Colorectal and Pancreatic Cancermentioning
confidence: 99%
“…Additionally, GRO has an important role in wound healing by modulating cell migration and angiogenesis as well. In particular, GRO-α seems to promote cancer proliferation, angiogenesis and metastasis (33,34). The dot blot assay revealed that wound fluid (WF) contains several factors that have mitogenic effects on cancer cells.…”
Section: Discussionmentioning
confidence: 99%